A Raman probe for selective wrapping of single-walled carbon nanotubes by DNA - Yang, Q; Gale, N; Oton, C; Li, F; Vaughan, A; Saito, R; Nandhakumar, I; Tang, Z; Cheng, H; Brown, T; Loh, W (2007)
In this paper, we discuss nanotube diameter selectivity in DNA wrapping of single-walled carbon nanotubes (SWNTs) under high-shear sonication and present Raman evidence for the selective wrapping. The DNA wrapping induces an upshift (an increase in wavenumber) of the radial breathing mode (RBM) bands in the Raman spectra of SWNTs, which indicates strong interaction between nanotubes and DNA. The extent of the upshift correlates well with the change in the intensity of the RBM bands upon DNA wrapping, and larger upshifts correspond to larger intensity changes. The intensity changes represent wrapping selectivity, and differ from tube to tube due to varying diameters and electronic properties. The shift of the RBM bands thus represents a practical probe for wrapping selectivity and the extent of the shifts indicates different electronic structures of core nanotubes hybridized with DNA. © IOP Publishing Ltd.